PENGARUH KEPEMILIKAN MANAJERIAL, LEVERAGE DAN INVESTMENT OPPORTUNITY SET TERHADAP KUALITAS LABA DENGAN KONSERVATISME SEBAGAI VARIABEL MODERATING (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2010-2014) - Rani Munik Munika; Amries Rusli Tanjung; Kamaliah Kamaliah (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2016)
The purpose of this research is to examine the influence of the factors that affectthe earnings quality, namely managerial ownership, Leverage and Investment Opportunity Set (IOS) which using conservatisme as an moderating variabel. This research used samples from 120 manufacturing companies listed on Indonesia Stock Exchange, by using purposive sampling method which were published financial report among 2010-2014. The analysis method of this research used moderate regression analisys. The results of this research show that(1) there is significant effect of managerial ownership on the earnings quality (2) there is significant effect of Leverage on the earnings quality ,(3) there is not significant effect of IOS on the earnings quality, (4) there is significant effect of managerial ownership on the earnings quality through conservatism (5) there is significant effect of Leverage on the earnings quality through conservatisme (6) there is not significant effect of IOS on the earnings quality through conservatisme